Study of Artworks from the Sukhothai Period in Thailand and the Yuan and Song Periods in China to Create Visual Artworks - Zong, Zongshaohan; Somthai , Pitiwat; Kanitwaranun, Suparirk (International Journal of Multidisciplinary in Management and Tourism, 2024)
This study aims to demonstrate the unique artistic style of illustration and a deep understanding and appreciation of these cultures through the fusion of Buddhist art from the Sukhothai period in Thailand and ink and landscape paintings from the Yuan and Song periods in China.Buddhist art of the Sukhothai period emphasizes the solemnity and sanctity of religious beliefs through the vivid display of Buddhist elements. Meanwhile, the ink and landscape paintings of the Yuan and Song dynasties add color to the illustrations, presenting natural and emotional expressions. The fusion of these two styles represents the harmonious coexistence of multiple cultures, emphasizing the complementarity and integration between different eras and cultures. Through this fusion of cultures, the illustrations provide viewers with a profound cultural experience, inspiring them to think about history and cultural heritage. The results of this study highlight the artistic and cultural value of Buddhist art from the Sukhothai period and ink landscape paintings from the Yuan and Song periods. This integration represents a deep understanding and appreciation of different cultural and artistic periods, blending the essence of different eras and further enriching the diversity of art.